Upaya Meningkatkan Minat Belajar Peserta Didik pada Materi Pengukuran Berbantuan Virtual Laboratorium OLABS pada Fase E SMAS Islam Darunnajah Sumenep - Herman Jufri Andi; Analiatus Shofiyah; Siska Siska; Syaiful Bahri; Moh Syamsul (Universitas Palangka Raya, 2025)
This research targets to increase college students' interest in studying physics with the help of OLABS media or virtual, the technique used is school room action research (PTK). Which entails cycles with meeting periods in every cycle. The difficulty of this study is elegance X college students with a complete of 15 college students. The records series method turned into accomplished using questionnaires and observations. based totally at the research that has been carried out in the pre-cycle degree, the average percentage of students' hobby in mastering physics became obtained through 60%, the